DEVELOPMENT OF STORE ATMOSPHERE ON CULINARY EFFORTTS TO INCREASE INTEREST IN BUYING PUBLIC, IN DISTRICT OF PERCUT SEI TUAN - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Currently, many businesses engaged in culinary efforts with a view from the simple to modern. Thus the competition faced by the culinary business operators will be even greater in term of attracting the attention of consumers.